IITA DG, Nteranya Sanginga, other senior management staff receive #Covid-19 #vaccine - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2021)
As part of intensive efforts to ensuring staff safety from the Covid-19 pandemic, IITA DG, Nteranya Sanginga, alongside other senior management team lead staff vaccination exercise at the International Institute of Tropical Agriculture (IITA) medical facility, Ibadan, Nigeria.